Locating hub container ports in the Eastern Mediterranean and the Black Sea through a hybrid simulation-analytical approach - Butun, Cihan (2014)
Containerized trade between Europe and Asia intensifies as global merchandise trade continues to thrive when the recent decades are concerned. As a consequence, frequent liner services are established on this trade route where the largest container ships of the fleets are employed. Another outcome of the intensive container movement is the establishment of hub-and-spoke networks around the trade routes. Hub-and-spoke networks in maritime transport bear the advantages of economies of scale, flexibility in shipping options and reduction of congestion at busy ports.